Numerical modeling of edfl and brillouin erbium fiber laser - Abd-Rahman, M.K.; Selvakennedy, S.; Ahmad, Harith (World Scientific Publ Co Pte Ltd, 2010)
Rigorous numerical models for the analysis of continuous wave operation of the erbium-doped fiber laser (EDFL) and Brillouin erbium fiber laser (BEFL) are demonstrated. The modeling of EDFL and BEFL (incorporating a non-linear gain medium), allows the behaviour of laser modes in their initial transient periods of operation to be analyzed. The analysis on competing modes in the laser cavity in determining the lasing wavelength, output power and spectral characteristics are not readily investigated via experimental approach. The results of the laser models in a steady state condition match acceptably well with the experimental data.